Consciousness as a Product of Evolution: Contents, Selector Circuits, and Trajectories in Experience Space - Lacalli, Thurston (Frontiers in Systems Neuroscience, 2021)
Conscious experience can be treated as a complex, unified whole, but to do so is problematic from an evolutionary perspective if, like other products of evolution, consciousness had simple beginnings, and achieved complexity only secondarily over an extended period of time as new categories of subjective experience were added and refined. The premise here is two-fold, first that these simple beginnings can be investigated regardless of whether the ultimate source of subjective experience is known or understood, and second, that of the contents known to us, the most accessible for investigation will be those that are, or appear, most fundamental, in the sense that they resist further deconstruction or analysis. This would include qualia as they are usually defined, but excludes more complex experiences (here, formats) that are structured, or depend on algorithmic processes and/or memory. Vision and language for example, would by this definition be formats. More formally, qualia, but not formats, can be represented as points, lines or curves on a topological experience space, and as domains in a configuration space representing the subset of neural correlates of consciousness (the selector circuits, or SCs) responsible for ensuring that a particular experience is evoked rather than some other. It is a matter of conjecture how points in SC-space map to experience space, but both will exhibit divergence, insuring that a minimal distance separates points in experience space representing different qualia and the SCs that evoke them. An analysis of how SCs evolve over time is used to highlight the importance of understanding patterns of descent among putative qualia, i.e. their homology across species, and whether this implies descent from an ancestral experience (i.e. an ur-quale) that combines modes of experience that later came to be experienced separately. The analysis also provides insight into the function of consciousness as viewed from an evolutionary perspective, defined here in terms of the access it provides to regions of SC-space that would otherwise be unavailable to real brains, to produce consciously controlled behaviors that would otherwise not occur.